Decision making in diamondback moth pest management strategies among cabbage farmers' in Cameron Highlands - M., Zurina; M. N., Mohd Roff; A., Azizan; A. B., Idris (AENSI Publisher, 2015)
The main purpose of this study was to analyse the decision making in diamondback moth (DBM) pest management strategies taken by cabbage farmers. This study employed the Theory of Planned Behaviour (TPB) and Technology Acceptance Model (TAM) to understand farmers’ specific attitudes (SA), subjective norms (SN) and perceived behavioural control (PBC) on the use of insecticides. The population consisted of farmers who used insecticide as their main DBM pest management strategy. The simple random sampling procedure was used to randomly select 370 cabbage farmers for this study in Cameron Highlands. Five point likert scale questionnaires were used for data collection. The data was collected through personal survey interview and then was analysed by using appropriate statistical procedures like descriptive statistics (mean, frequency, percent) and inferential statistics (correlation and regression) of the SPSS software. The result indicated the intention, SA, SN, PBC of farmers to use insecticides to control DBM in the coming season was at a moderate level. The result also showed that there was a significant relationship between SA, SN, PBC and the intention to apply insecticide in the coming season. PBC was the most important factor in influencing behavioural intention, followed by SA and NS. Thus, results of the TPB and TAM suggest that the models can provide a useful insight on farmers’ decision-making processes behaviour.